Cinnamaldehyde, but Not Thymol, Counteracts the Carboxymethyl Cellulose-induced Growth Depression in Female Broiler Chickens - Lee, K.-W.; Everts, H.; Kappert, H.J.; Wouterse, H.; Frehner, M.; Beynen, A.C. (International Journal of Poultry Science, 2004)
The question addressed was whether dietary essential oils could antagonize the negative effect of Carboxymethyl cellulose (CMC) on growth performance in broilers. Diets without or with 1% CMC, and CMC containing diet with either 100 ppm thymol, cinnamaldehyde or a commercial essential oil blend were fed to female broiler chickens for 40 days. Chicks receiving the CMC diet showed significantly depressed weight gain for the period of 0 - 21 days. Addition of cinnamaldehyde or commercial essential oil to the CMC diet partially counteracted the negative effect on growth performance. Group mean feed intake was lower in CMC-fed chicks, but was raised when cinnamaldehyde or the commercial oil was added to the diet. Intestinal viscosity was increased by CMC inclusion, but was not lowered by the additives. Fat digestibility was significantly reduced by CMC, but cinnamaldehyde or commercial oil inclusion partially reversed this effect. This study indicates that cinnamaldehyde, but not thymol, may antagonize the negative effects of CMC on growth performance which may relate to improving fat digestibility.